Financial Crises and Social Spending : The Impact of the 2008-2009 Crisis - Lewis, Maureen (World Bank, Washington, DC, 2013)
This paper examines the impacts of the 2008-2009 economic crisis on social spending, drawing on evidence at the global, national, and household levels, to provide a sense of the nature and the effects of the worldwide downturn on spending in the social sectors. It summarizes existing empirical evidence on the relationship between crises, or other serious dislocations on education, health, HIV/AIDS, and nutrition as background to the analysis of growth and social spending. The paper analyzes the relationship between GDP growth, growth in education and health spending, and projects expenditure responses to 2012, to illustrate how expected changes in future economic growth are likely to affect both absolute spending and growth in social expenditures. It provides an analysis of the effects on HIV/AIDS spending, a relatively new funding category and therefore outside the purview of the econometric analysis. It examines the responsiveness of Overseas Development Assistance (ODA) to financial crises in terms of subsequent allocations from the developed world, and the impacts on ODA spending for education and health in developing and transition countries. The paper concludes by citing existing evidence on regional impacts of the crisis on public spending, and the effects on household budgets in Eastern Europe and Central Asia, the region hardest hit by the current crisis.